E-MODULE DEVELOPMENT FOR THE SUBJECT OF MEASURING INSTRUMENTS AND MEASUREMENT IN ELECTRONICS ENGINEERING EDUCATION - Nuryake Fajaryati; Nurkhamid Nurkhamid; Ponco Wali Pranoto; Muslikhin Muslikhin; Athika Dwi W (Faculty of Engineering, Universitas Negeri Yogyakarta, 2016)
This study aims to develop an e-module as a medium of learning for the practice course of Measuring Instruments and Measurement in the Department of Electronics Engineering Education of Yogyakarta State University and to determine the feasibility of the e-module. This study employed a method of research and development. The development process was conducted through four phases by using the model of Lee and Owens which consisted of analysis phase, design phase, developing and implementation phase, as well as evaluation phase.The evaluation was conducted in several stages. Firstly, an alpha test for product validation was conducted by the experts on material and media. After that, a beta test was conducted by testing the product in small group users. The subjects of this study were the students of Electronics Engineering. The instruments used to collect the data were a validation sheet and questionnaires. The results of qualitative data were then modified into quantitative data with a range of 1 to 5, then they were converted with a rating scale to determine the feasibility of the medium. The results showed that based on the alpha test, the medium was in a very high quality. Meanwhile, in the beta test of the instructional aspect, in terms of material and evaluation and the multimedia aspect the e-module was respectively considered feasible and quite feasible. The four indicators namely text, image, animation and video were all generally considered feasible. In terms of usage aspect, the e-module was considered feasible where its two indicators, namely instructions and navigation, were generally regarded as very feasible by all respondents.